Control of the nucleation and growth processes of metal–organic frameworks using a metal ion-doped polymer substrate for the construction of continuous films. Issue 33 (25th July 2019) - Ohhashi, Takashi; Tsuruoka, Takaaki; Takashima, Yohei; Akamatsu, Kensuke
Abstract : Densely-packed continuous MOF crystal-based films can be prepared by controlling the nucleation and growth processes. Abstract : We herein demonstrate a novel concept for the one-pot synthesis of metal–organic framework (MOF) films on a metal ion-doped polymer substrate based on control of the nucleation and growth processes. This strategy allows the ready fabrication of densely-packed uniform MOF films.